An estimate of best approximation by angle of sum of double series with respect to multiplicative system with quasiconvex coefficients - Bokayev, N.A.; Syzdykova, A.T. (Bulletin of the Karaganda University. Mathematics Series, 2015)
In this work double series with respect to multiplicative systems in terms of quasiconvex coefficients are investigated. The convergence such series to integrable functions are proved and an estimate of best approximation by angle with respect to multiplicative system in L1[0,1)2 metric is obtained.